STRUKTUR DAN MAKNA MANTRA DALAM UPACARA BALALA DAYAK BAKATI DAN RENCANA IMPLEMENTASI DALAM PEMBELAJARAN SASTRA - Bagong, Virminus; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe researcher was interested in examining the mantra of Balala Dayak Bakati ceremony in Teriak district, Bengkayang district, because the researchers wanted to know the elements that built the mantra sound, besides that the researchers wanted to know the spelling, diksi, rima and Balala DayakBakati spells.The problem in this research can be broken down into several sub-problems, namely the spelling story environment, mantra diction, spell rhyme, meaning in the mantra, and the implementation plan for learning Indonesian. The theory on which this research is based is a theory related to the structure of folk poetry, especially spells. The theory includes (1) rima theory, (2) poetry type theory, (3) diction theory, (4) meaning theory, (5) storytelling environmental theory, (6) learning implementation theory. The research methodology applied by researchers is a descriptive method and a qualitative research form with a structural approach.Keywords: Mantra balala, Dayak Bakati, Structure, MeaningAbstractThe researcher was interested in examining the mantra of Balala Dayak Bakati ceremony in Teriak district, Bengkayang district, because the researchers wanted to know the elements that built the mantra sound, besides that the researchers wanted to know the spelling, diksi, rima and Balala DayakBakati spells.The problem in this research can be broken down into several sub-problems, namely the spelling story environment, mantra diction, spell rhyme, meaning in the mantra, and the implementation plan for learning Indonesian. The theory on which this research is based is a theory related to the structure of folk poetry, especially spells. The theory includes (1) rima theory, (2) poetry type theory, (3) diction theory, (4) meaning theory, (5) storytelling environmental theory, (6) learning implementation theory. The research methodology applied by researchers is a descriptive method and a qualitative research form with a structural approach.Â Keywords: Mantra balala, Dayak Bakati, Structure, Meaning.